2016
DOI: 10.1186/s13006-017-0105-1
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding woman are at higher risk of vitamin D deficiency than non-breastfeeding women - insights from the German VitaMinFemin study

Abstract: BackgroundDespite increased awareness of the adverse health effects of vitamin D deficiency, only a few studies have evaluated the vitamin D status (25-hydroxyvitamin D [25(OHD)]) of breastfeeding women and up to now, no information exits for German breastfeeding women. Therefore, the aim of study was to determine the vitamin D status of breastfeeding women compared to non-pregnant and non-breastfeeding (NPNB) women.MethodsThis cross-sectional study investigated 124 breastfeeding women and 124 age and season m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 46 publications
0
19
2
3
Order By: Relevance
“…In previous studies, human breastmilk has been reported to be a very poor source of vitamin D and typically contains 5-136 IU/L, even for breastfeeding mothers in an environment with abundant sunlight [23,33]. In addition, breastfeeding women are at higher risk of VDD than nonbreastfeeding women in a German VitaMinFemin study [34]. In our observation, although we did not analyze the vitamin D concentration in breastmilk, breastfeeding infants had a higher incidence of VDD.…”
Section: Discussioncontrasting
confidence: 52%
“…In previous studies, human breastmilk has been reported to be a very poor source of vitamin D and typically contains 5-136 IU/L, even for breastfeeding mothers in an environment with abundant sunlight [23,33]. In addition, breastfeeding women are at higher risk of VDD than nonbreastfeeding women in a German VitaMinFemin study [34]. In our observation, although we did not analyze the vitamin D concentration in breastmilk, breastfeeding infants had a higher incidence of VDD.…”
Section: Discussioncontrasting
confidence: 52%
“…Low vitamin D intakes in our study population of pregnant women and lactating women are explained by the limited food sources for vitamin D and the limited consumption of foods fortified with vitamin D (the latter results from the fact that the Belgian market of foods fortified with vitamin D is limited and mainly targets children and adolescents [ 16 , 54 ]). The consumption of vitamin D-containing supplements did not contribute to an adequate intake of vitamin D, despite high supplement compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Health Canada [ 10 ] and the Institute of Medicine (IOM) [ 11 ] have recommended 600 International Units (IU)/day of vitamin D for pregnant and breastfeeding women and 400 IU/day for infants, with the goal of achieving sufficient vitamin D status in the infant. However, studies in pregnant and breastfeeding mothers have shown a large proportion of these women having suboptimal vitamin D status despite reporting intakes that meet these recommendations [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%